Pelatihan Pembelajaran Tematik Terintegrasi dengan Karakter Melalui Lagu dan Aransemen bagi Guru Sekolah Dasar Muhammadiyah Adiwerna: Training on Integrated Thematic Learning with Character Building Through Songs and Arrangements for Teachers at Muhammadiyah Adiwerna Elementary School - Darodjat Darodjat; Zakiyah Zakiyah; Pratik Hari Yuwono; Muhammad Sidik Pambudi; Asih Hidayatun; Fina Aulia Fajrin; Hasyifa Ratna Astria (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Elementary school teachers often face limitations in developing character-integrated thematic learning using creative media, particularly self-composed songs and musical arrangements. This community service program aimed to enhance teachers’ knowledge and skills in designing character-integrated, theme-based learning through songs and musical arrangements at Budi Mulia Muhammadiyah Elementary School in Adiwerna. The program employed socialization, counseling sessions, workshops on writing thematic song lyrics, hands-on musical arrangement training using free software, and mentoring. The participants consisted of 8 elementary school teachers. Evaluation was conducted using pre- and post-activity response questionnaires and product assessment. The results indicated an 83% increase in teachers’ understanding of character-integrated thematic learning, a 78% improvement in song lyric composition skills, and a 72% increase in basic musical arrangement skills. Teachers also produced sample songs and arrangements applicable to lower-grade classrooms. This program strengthens teachers’ capacity to develop innovative and sustainable learning media.